Dioxin receptor and SLUG transcription factors regulate the insulator activity of B1 SINE retrotransposons via an RNA polymerase switch - Román, Angel Carlos; González-Rico, Francisco J.; Moltó, Eduardo; Hernando, Henar; Neto, Ana; Vicente-Garcia, Cristina; Ballestar, Esteban; Gómez-Skarmeta, José L.; Vavrova-Anderson, Jana; White, Robert J.; Montoliu, Lluís; Fernández-Salguero, Pedro M. (Genome Research, 2011)
Complex genomes utilize insulators and boundary elements to help define spatial and temporal gene expression patterns. We report that a genome-wide B1 SINE (Short Interspersed Nuclear Element) retrotransposon (B1-X35S) has potent intrinsic insulator activity in cultured cells and live animals. This insulation is mediated by binding of the transcription factors dioxin receptor (AHR) and SLUG (SNAI2) to consensus elements present in the SINE. Transcription of B1-X35S is required for insulation. While basal insulator activity is maintained by RNA polymerase (Pol) III transcription, AHR-induced insulation involves release of Pol III and engagement of Pol II transcription on the same strand. B1-X35S insulation is also associated with enrichment of heterochromatin marks H3K9me3 and H3K27me3 downstream of B1-X35S, an effect that varies with cell type. B1-X35S binds parylated CTCF and, consistent with a chromatin barrier activity, its positioning between two adjacent genes correlates with their differential expression in mouse tissues. Hence, B1 SINE retrotransposons represent genome-wide insulators activated by transcription factors that respond to developmental, oncogenic, or toxicological stimuli.
10.1101/gr.111203.110